Utilization of Papaya Leaves (Carica papaya) in Feed on Growth of Catfish (Clarias sp.) in Muara Enim, South Sumatera - Muhamad Sidiq Irsyadil Firdaus; Retno Cahya Mukti (IJOTA (Indonesian Journal of Tropical Aquatic), 2021)
The feed must have a quality that matches the needs of the fish to produce high fish growth. Feed quality can be improved by adding alternative ingredients to feed. One alternative material that can be used is papaya leaves. The purpose of this study was to determine the effect of adding papaya leaves to feed on the growth of catfish (Clarias sp). This research was conducted in Muara Enim, South Sumatra in August 2020. The treatments were P0: control (without adding papaya leaves) and P1: with the addition of papaya leaves. The data observed included absolute growth, specific growth rate, feed efficiency, and survival. Fish maintenance data that obtained in treatment P0, that absolute weight growth of 8.43 g, absolute length growth 5.13 cm, specific growth rate 6.41 %, feed efficiency 95.77 %, and survival 76 %, while in P1 treatment using leaves papaya produced absolute weight growth of 10.57 g, absolute length growth of 5.17 cm, the specific growth rate of 5.84 %, feed efficiency 100.83 %, and survival 60 %. The results obtained indicate that the provision of papaya leaves affects the growth of catfish.